1994
DOI: 10.1007/s002920050040
|View full text |Cite
|
Sign up to set email alerts
|

Das Normgewicht des Gehirns beim Erwachsenen in Abh�ngigkeit von Alter, Geschlecht, K�rpergr��e und Gewicht

Abstract: Based on more than 8000 autopsies of male and female patients without brain diseases the normal brain weight of adult males and females in relation to sex, age, body-weight, and body-height as well as Body Mass Index were calculated. The average brain weight of the adult male was 1336 gr; for the adult female 1198 gr. With increasing age, brain weight decreases by 2.7 gr in males, and by 2.2 gr in females per year. Per centimeter body height brain weight increases independent of sex by an average of about 3.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 0 publications
3
32
0
1
Order By: Relevance
“…When the sexes are combined, however, there is a slight decline of brain weight, perhaps of about the same magnitude as that observed in humans (Dekaban and Sadowsky, 1978;Hartmann et al, 1994); this small loss in the chimpanzee is about 1.1 g, or 0.3%, per year over the period from adolescence to old age.To evaluate whether this apparent decline with age may simply reflect the shorter life span and larger brain of the male, we conducted an additional analysis in which the effect of age was evaluated after the effect of sex had been statistically removed. When the sexes are combined, however, there is a slight decline of brain weight, perhaps of about the same magnitude as that observed in humans (Dekaban and Sadowsky, 1978;Hartmann et al, 1994); this small loss in the chimpanzee is about 1.1 g, or 0.3%, per year over the period from adolescence to old age.To evaluate whether this apparent decline with age may simply reflect the shorter life span and larger brain of the male, we conducted an additional analysis in which the effect of age was evaluated after the effect of sex had been statistically removed.…”
Section: Discussionmentioning
confidence: 66%
“…When the sexes are combined, however, there is a slight decline of brain weight, perhaps of about the same magnitude as that observed in humans (Dekaban and Sadowsky, 1978;Hartmann et al, 1994); this small loss in the chimpanzee is about 1.1 g, or 0.3%, per year over the period from adolescence to old age.To evaluate whether this apparent decline with age may simply reflect the shorter life span and larger brain of the male, we conducted an additional analysis in which the effect of age was evaluated after the effect of sex had been statistically removed. When the sexes are combined, however, there is a slight decline of brain weight, perhaps of about the same magnitude as that observed in humans (Dekaban and Sadowsky, 1978;Hartmann et al, 1994); this small loss in the chimpanzee is about 1.1 g, or 0.3%, per year over the period from adolescence to old age.To evaluate whether this apparent decline with age may simply reflect the shorter life span and larger brain of the male, we conducted an additional analysis in which the effect of age was evaluated after the effect of sex had been statistically removed.…”
Section: Discussionmentioning
confidence: 66%
“…This value is in the range of normal water-soluble brain Aβ concentrations reported in the literature. 26 Using the sex-weighted average brain mass for our population of 10 females and 1 male (1211 g) 27 and assuming homogeneity: [normalAnormalβ]×brain mass=64100.2emnormalpg/normalg×12110.2emnormalg=77600.2emnormalngestimates the soluble Aβ peptide pool size in the normal brain. The turnover rate of Aβ peptides is then: 77600.2emnormalng×0.140.2emh1=18.10.2emnormalng/normalmin…”
Section: Resultsmentioning
confidence: 99%
“…Dekaban and Sadowsky (1978) and Hartmann et al (1994) reported a trend toward lower brain weight with increasing age in humans, with an increase in the rate of decline at about 50 years. In general, brains of 70 -80-year-olds weigh about 7% less than those of 20-year-olds of comparable body weight (Dekaban and Sadowsky, 1978;Hartmann et al, 1994;Pakkenberg and Voigt, 1964;Chrzanowska and Beben, 1973). From ages 26 -80, brain weight declines by about 2 g per year (Ho et al, 1980a,b).…”
mentioning
confidence: 94%